Lethal malformations and perinatal mortality: a 10 year review with comparison of ethnic differences. - Young, I D (1987)
During 1976 to 1985 perinatal mortality in Leicestershire decreased from 21 to 9.5 per 1000 births. Throughout this period the incidence of lethal malformations, excluding neural tube defects, remained relatively constant at around 1.8 per 1000 births. Analysis of the malformations present in 201 lethally malformed babies showed that 147 (73%) had a disorder carrying a recurrence risk of 1% or greater. Only 7% of these malformations might have been predicted from the family history or advanced maternal age. The incidence of lethal malformations was significantly increased in the Asian population, largely because of an excess of autosomal recessive disorders. The contribution of lethal malformations to perinatal mortality has almost doubled over the past 10 years and is likely to increase despite prenatal diagnosis and improvements in obstetric and paediatric services.